Molecular Characterization and DNA Fingerprinting of Xanthomonas oryzae pv. oryzae Isolates from Climate Change Prone Areas in East Africa - Onasanya, A.; Kiepe, P.; Basso, A.; Nkima, G.; Nwilene, F.E.; Ingelbrecht, I.L.; Lamo, J.; Ekperigin, M.M.; Onasanya, R.O.; Oyelakin, O.; Winter, S.; Sere, Y. (Science Alert, 2011)
Genomic DNA fingerprinting is a useful tool for effective and reliable identification and differentiation of Xanthomonas oryzae pv. oryzae (Xoo) pathogen from rice. The study aimed to conduct molecular characterization and DNA fingerprinting of 23 Xoo isolates from East Africa and two Xoo isolates from IRRI (Philippines) as control. PCR analysis was carryout on genomic DNA of 25 Xoo isolates using 6 Xoo specific primer pairs. Cluster analyses of genetic data obtained from 25 Xoo DNA fingerprints revealed two major genotypes (GrpA and GrpB) among the 25 Xoo isolates. GrpA has three subgroups (GrpA1; GrpA2; GrpA3) and GrpB (GrpB1; GrpB2; GrpB3). GrpA genotype consists of 20 Xoo isolates from Uganda, Rwanda and Philippines while GrpB genotype has 5 Xoo isolates from Rwanda. Some Xoo isolates were identical (PX-1, PX-2; UX621, RX2101; RX554, UX623, RX4113; UX211, UX213, UX214, RX4112, UX215). The emergence of subgroup genotypes could possibly be due to mutations and interactions among isolates and strains in host cells. Some Xoo isolates from Rwanda and Uganda were identical suggesting possible pathogen migration between these countries and long-term survival. Durable resistance rice cultivars would need to overcome both GrpA and GrpB Xoo genotypes in order to survive after their deployment into different rice ecologies in East Africa